PELATIHAN PENGUATAN KELOMPOK BANJAR SEBAGAI PENUNJANG KEMANDIRIAN EKONOMI MASYARAKAT DI DUSUN KEMBANG KUNING DESA GERIMAK INDAH KECAMATAN NARMADA LOMBOK BARAT - Ihromi, Syirril; Nurhayati, Nurhayati; Asmawati, Asmawati; Putri, Dina Soes; Dewi, Earlyna Sinthia (Jurnal Agro Dedikasi Masyarakat (JADM), 2021)
Gerimak Indah Village is a border village located between West Lombok district and Mataram City, which has the potential of abundant natural resources, but the lack of community knowledge in post-harvest techniques of agricultural products, processing agricultural products causes the economy in the village, one of which is the yellow flower hamlet. not yet prosperous, so this activity aims to improve the knowledge and skills of partners about the processing of food products based on rice waste (bran). The implementation method goes through the following stages: (1) Submission of materials (2) demonstration and manufacture of product cookies made from bran and mung bean (3) sensory testing of various processed products (4) evaluation of the success of program activities. The results of the activity showed that there was an increase in partner knowledge and skills smoothly and effectively the time used and responded positively to this activity. It is hoped that the knowledge and skills obtained will be a provision to be able to meet the nutritional needs of the family as well as to build a pioneering business.